Gastric paraganglioma: a case report and review of literature - Hu, Chengyu; Luo, Bixian; Hong, Bo; Zhang, Mingqi; Wu, Zelai; Zhu, Xiuliang; Luan, Fengming; Huang, Yi; Gong, Weihua (Frontiers in Oncology, 2024)
Paragangliomas (PGLs) are rare neuroendocrine tumors which overproduce catecholamines (CAs). They are extra-adrenal, catecholamine-secreting tumors occurring outside the adrenal glands. Gastric PGLs originating from extra-adrenal paraganglia are exceptionally rare, and their presentation in geriatric patients further adds to the complexity of diagnosis and management. A 72-year-old male patient presented with enduring left upper abdominal pain and anemia persisting for over a year, and hypertension for six months. Physical examination revealed epigastric discomfort and pallor. Computed tomography scans revealed enlarged lymph nodes in the lesser curvature of the stomach and thickening of the gastric antrum wall with concavity. The patient underwent three cycles of neoadjuvant therapy before radical gastrectomy for gastric cancer. These imaging findings were confirmed during surgery and intraoperative blood pressure was in fluctuation. After the successful resection of the tumor, postoperative pathology confirmed paraganglioma. During postoperative examination, it was observed that the patient's CAs and their metabolites had returned to within the normal range.Combined with the existing ten literatures, we retrospective report the clinical and pathological characteristics and treatment strategies of the rare gastric paraganglioma.PGLs are uncommon neuroendocrine tumors originating from neural crest cells within the sympathetic and parasympathetic nervous systems (1). They are typically classified into sympathetic and parasympathetic subtypes, with most sympathetic subtypes being functional, secreting CAs. In patients with catecholamine hypersecretion, most tumors locate at the